Persepsi Generasi Z terhadap Edukasi Perpajakan melalui Media Sosial: Studi pada Digital Natives di DKI Jakarta - Exita Hanum Syahrial; Harefa, Jeanne Veren (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study analyzes Generation Z's perception of tax education through social media in the DKI Jakarta area. The main focus of the research is to understand how Generation Z as digital natives view and respond to tax education content presented through social media platforms such as Instagram and TikTok. The research employs a mixed-method approach with a sequential explanatory design, combining quantitative methods through online surveys of Generation Z aged 18-27 years and qualitative methods through DGT social media content analysis. The results show that 70% of Generation Z have a positive perception of tax education through social media, while 30% show negative perceptions. Visual content and short videos received the most positive response with an engagement rate of 75%, while the relevance level of content to target audience needs reached 65%. The Instagram platform shows an engagement rate of 5.8%, slightly higher than TikTok which reaches 4.2%. The study identifies several key challenges such as Generation Z's short attention span (average 8 seconds), the complexity of tax information, and low engagement rates. To address these challenges, a more interactive and relevant content development strategy is needed, tailored to the characteristics of Generation Z as digital natives. This research provides strategic recommendations to improve the effectiveness of tax education through social media, including optimization of posting times, content formats, and increased interactivity to encourage active audience engagement.